Trade and Labor Outcomes in Latin America's Rural Areas: A Cross-Household Surveys Approach - Leonardo Gasparini; Federico Gutiérrez; Guido G. Porto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This paper explores the potential link between trade and labor outcomes in rural areas in Latin America by estimating cross household-survey regression models with microdata from 60 Latin American household surveys and country aggregate data. We find a significant positive association between labor outcomes in rural areas and some measures of international trade, in particular exports, trade as a share of GDP, and the price of exports. International trade has been associated with higher wages and labor income in rural areas, in particular for those workers located in the bottom quantiles of the conditional wage distribution. Instead, our results suggest that all individuals in rural areas benefit about the same due to higher export prices. Results for urban areas are rarely statistically significant.
Keywords: F02; F16; J31; J43; 330; trade; wages; labor; rural; Latin America